Health Technology Assessment: informed by science or in the service of politics? - Patrícia Coelho De Soárez (Universidade de São Paulo, 2021)
ABSTRACT The youth of Health Technology Assessment (HTA), as an institutional policy at the national level, signals the need to reflect on how its implementation took place under the perspective of its insertion in health policy and the scientific field. At the end of its first decade, these questions arise: has HTA translated into a health policy informed by science? Has its scientific foundation been used in the service of politics? To understand this political process, we apply the multiple-streams framework formulated by John Kingdon. The use of science to inform policy and the political use of science present themselves in an unstable balance. The survival of this policy will depend not only on science but on the art of orchestrating the interests of various agents so that HTA becomes a health policy for strengthening and sustainability of SUS.